Teacher Adaptation in Science Curriculum Development: Enhancing Student Learning Satisfaction - Sapruni Sapruni; Fauzan Amin (STAI Hubbulwathan Duri, 2025)
The ability to develop science-based curriculum content is essential to ensuring effective and relevant science education. This study investigates the impact of teacher adaptation in curriculum development on student learning satisfaction. A quantitative approach with a descriptive survey method was employed. The study was conducted at MTsN 1 Bengkulu City, involving 120 students, with a randomly selected sample of 50 eighth-grade students. Data were collected using a Likert-scale questionnaire (1–5). Instrument validity was assessed using the Aiken index, and reliability was determined through Cronbach's alpha. Data were analyzed using a t-test for mean differences, preceded by normality and homogeneity tests. Findings indicate that the average teacher adaptation score was higher than the student learning satisfaction score. Statistical analysis yielded a t-value of 5.473 and a p-value of 0.000 ( 0.05), demonstrating a significant positive effect of teacher adaptation on student learning satisfaction. The results suggest that when teachers effectively adapt curriculum content to meet student needs, learning satisfaction improves. This highlights the importance of teacher training and professional development programs in curriculum design. Teacher adaptation significantly influences student learning satisfaction, underscoring the need for policies supporting teacher training and curriculum development. Future research should explore additional factors influencing student learning outcomes.